Biological surface modification of titanium surfaces using glow discharge plasma. - Huang HM; Hsieh SC; Teng NC; Feng SW; Ou KL; Chang WJ; Huang, Haw-Ming; Hsieh, Sung-Chih; Teng, Nai-Chia; Feng, Sheng-Wei; Ou, Ken-Liang; Chang, Wei-Jen (Medical & Biological Engineering & Computing, 2011)
To improve the biological activity of titanium, by using of glow discharge plasma (GDP), albumin-grafted titanium disk have been implemented and carefully studied. Titanium disks were pre-treated with GDP in an environment filled with argon and allylamine gas. Glutaraldehyde was used as a cross-linking agent for albumin grafting. Then, the surface of the albumin-grafted titanium was examined using scanning electron microscopy and X-ray photoelectron spectroscopy. In addition, the static water contact angles of the albumin-grafted titanium disks were measured using goniometry. To observe the effects of albumin adsorption on cell behavior, MG-63 osteoblast-like cells were cultured on the surface-modified titanium disks. Blood coagulation resistance of the modified titanium was monitored and compared to the control titanium disks. The results demonstrated that MG-63 osteoblast-like cells cultured on the albumin-grafted titanium disks expressed better-differentiated morphology compare to cells grown on the control disks. Furthermore, albumin-grafting treatment significantly improved the surface wettability of the titanium disks and resulted in a significantly negative effect on thrombus formation. Based on these results, it was believed that the GDP can potentially improve the biofunctionality of titanium surfaces.